Phase Tandem Low-Coherence Interferometry for Surface Vibration Measurements - Petr Volkov; Alexander Bobrov; Alexander Goryunov; Mark Kovrigin; Andrey Lukyanov; Daniil Semikov; Oleg Vyazankin (Sensors)
The development of optical methods for surface vibration measurements is currently of great interest. We propose a modified tandem low-coherence technique that utilizes the phase information of the low-coherence signal to detect surface vibrations. The resolution of this scheme is less than 1 nm for a 20 kHz bandwidth. The proposed technique is not just limited to measurements of surface vibrations, but it can also be used for interferometric fiber-optic sensors.